Effect of Alginate Lyase on Biofilm-Grown Helicobacter pylori Probed by Atomic Force Microscopy. (6th May 2015) - Maiorana, Alessandro; Bugli, Francesca; Papi, Massimiliano; Torelli, Riccardo; Ciasca, Gabriele; Maulucci, Giuseppe; Palmieri, Valentina; Cacaci, Margherita; Paroni Sterbini, Francesco; Posteraro, Brunella; Sanguinetti, Maurizio; De Spirito, Marco
Abstract : Helicobacter pylori ( H. pylori ) is a microorganism with a pronounced capability of adaptation under environmental stress solicitations. Its persistence and antimicrobial resistance to the drugs commonly used in the anti- H. pylori therapy are associated with the development of a biofilm mainly composed of DNA, proteins, and polysaccharides. A fundamental step to increase the success of clinical treatments is the development of new strategies and molecules able to interfere with the biofilm architecture and thus able to enhance the effects of antibiotics. By using Atomic Force Microscopy and Scanning Electron Microscopy we analyzed the effects of the alginate lyase (AlgL), an enzyme able to degrade a wide class of polysaccharides, on the H. pylori shape, surface morphology, and biofilm adhesion properties. We demonstrated that AlgL generates a noticeable loss of H. pylori coccoid form in favor of the bacillary form and reduces the H. pylori extracellular polymeric substances (EPS).